THE RELATIONSHIP BETWEEN BANK PROFITABILITY AND ECONOMIC GROWTH FOR CONVENTIONAL BANKS IN GCC COUNTRIES - Walid Ali; Wissem Ben Ali; Amal Salah (Journal of Smart Economic Growth, 2022)
Does bank profitability encourage economic growth? Even while it seems like political leaders are quite concerned about the low level of bank profitability, it is still unclear how bank profitability affects economic growth. It might help economic growth and financial stability, but it could also reduce competition and, as a result, slow down economic progress.  We present the first empirical study to evaluate how bank profitability affects economic growth. Using the Generalized Method of Moments (GMM), we build an econometric model for 72 conventional banks across six countries from GCC region from 2000 to 2019. We find that the profitability of the banks has a positive short- and long-term impact on economic growth. For regulating the dynamics of bank profitability, these findings are trustworthy. Additionally, they are sensitive to deadlines, restrictions, and exchange measures.